Alcohol consumption practices among Nepali migrant workers in Shah Alam, Selangor - Hasanain Faisal Ghazi; Mohammed A. AbdalQader; Mohammed Faez Baobaid; Indang Ariati Ariffin; Mariam-Aisha Fatima; Afrisya Adlina Mohd Azhar; Muhammad Mukhlis Ma’arof; Hasan, Tiba Nezar; Mohd Rohaizat Hassan (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Malaysia has been considered an industrialized country and there is a demand for manpower in low-skilled jobs which usually filled by migrant workers. Therefore, this study focused to identify the level of alcohol consumption and its associated factors among Nepali migrant workers in Shah Alam, Selangor. A cross-sectional study using a convenient sampling method was conducted among 233 Nepali migrant workers in Shah Alam, Selangor using a self-administered questionnaire. A validated questionnaire (The Alcohol Use Disorder Identification Test) by WHO was used in the study. The results showed that 60.09% of Nepali workers consumed alcohol with most of them are in low (31.43%) and medium (29.28%) risk level for alcohol consumption. The empirical findings revealed a significant association between income, education level, and peer pressure with alcohol consumption (p value <0.001 respectively). However, the study found no association between age, marital status, years of working, and body mass index with alcohol consumption (p value= 0.44, 0.19, 0.42, 0.40 respectively). In conclusion, most Nepali migrant workers consumed alcohol but in low and medium risk severity. The results highlighted socio-demographic factors such as income and education as well as peer pressure among the important factors affecting alcohol consumption. Thus, it is important to address this issue by creating awareness by conducting health talk and campaign. This can give a clear idea to migrant workers on the health effect of alcohol consumption. More education and promotion are needed to address the health effect of excessive alcohol consumption and work productivity among migrant workers in their own language.